2019
DOI: 10.1111/jonm.12812
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal learning outcomes of using different teaching sequences in a nursing administration project

Abstract: Aim:To examine the effects of using different teaching sequences on knowledge acquisition, knowledge retention, self-directed learning and teamwork in a nursing administration project.Background: Compared to other professional courses, nursing administration is relatively difficult, and it is important for nursing administration students to spend long hours working in hospitals. As such, better teaching strategies utilizing proper sequencing may yield better learning outcomes for students. Methods:A longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 32 publications
0
6
0
6
Order By: Relevance
“…En 55 % de las investigaciones se utilizaron las estrategias: aprendizaje basado en problemas, estudios de caso o la problematización como metodología para la enseñanza y aprendizaje de la asignatura de gestión, ya sea en la práctica [17][18][19][20] o en la teoría [21][22][23][24][25][26] . De estos, dos artículos agregaron el aprendizaje basado en lecturas 21 y juego de roles 24 como otras estrategias de enseñanza, mientras que 11 % usó el portafolio de evidencia en el aprendizaje autodirigido 27,28 . Únicamente 6 % utilizó la simulación con juegos de rol 29 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…En 55 % de las investigaciones se utilizaron las estrategias: aprendizaje basado en problemas, estudios de caso o la problematización como metodología para la enseñanza y aprendizaje de la asignatura de gestión, ya sea en la práctica [17][18][19][20] o en la teoría [21][22][23][24][25][26] . De estos, dos artículos agregaron el aprendizaje basado en lecturas 21 y juego de roles 24 como otras estrategias de enseñanza, mientras que 11 % usó el portafolio de evidencia en el aprendizaje autodirigido 27,28 . Únicamente 6 % utilizó la simulación con juegos de rol 29 .…”
Section: Resultsunclassified
“…Estudios como los llevados a cabo por Nkosi 17 en Sudáfrica; Kaiser 18 , Gomes 19 , Opptiz 20 y Meyenberg 21 en Brasil; Ancel 22 y Goktepe 26 en Turquía; Lin 21 en China, así como Jang y Park 23 en Japón, han demostrado que el uso del método de ABP en programas de gestión favorece al desarrollo de habilidades interpersonales, sobre todo en materia de comunicación [17][18][19][20][21]25 , liderazgo 19,20,[24][25][26] , trabajo en equipo [21][22][23][24] y relaciones interpersonales 18,19 . También incrementa las habilidades analíticas [17][18][19][20][22][23][24] (especialmente aquellas relacionadas con la planificación de recursos humanos y materiales).…”
Section: Aprendizaje Basado En Problemasunclassified
See 1 more Smart Citation
“…Some studies, such as those carried out in South Africa, Brazil, Turkey, China and Japan, have shown that using the PBL method in management programs contributes to the development of interpersonal skills, especially communication skills ( 25 - 29 ) , leadership ( 25 , 28 , 30 - 32 ) , teamwork ( 27 , 30 ) and interpersonal relationships ( 28 - 29 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It also develops skills in continuous improvement topics ( 30 , 34 ) . In the same way, action-related skills are developed, but to a lesser extent, and are associated with being able to establish, organize and evaluate goals/objectives and make timely and risk-free decisions in problematic situations ( ( 27 , 29 - 30 , 32 , 35 ) . Finally, the least developed skill is use of the information, such as collecting and analyzing the hospital environment data ( ( 30 , 34 ) .…”
Section: Introductionmentioning
confidence: 99%